2013
DOI: 10.1177/0888406412473311
|View full text |Cite
|
Sign up to set email alerts
|

Honoring Voices From Beginning Special Educators for Making Changes in Teacher Preparation

Abstract: Through a mixed-methods study, teacher educators investigated recent graduates' perceptions of their preparation program. Beginning special education teachers completed surveys and indicated (a) their level of preparation and confidence associated with 25 core competencies, (b) the most beneficial components of their preparation program, (c) suggestions for improving the program, and (d) current training needs. The highest levels of preparation and confidence were found in the areas of professionalism, behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 24 publications
5
30
0
Order By: Relevance
“…They argue that well planned coursework and exposure to practical hands-on experiences play a crucial role in fostering favourable attitudes and perceptions of pre-service physical education teachers towards working with students with disabilities. Similar findings were revealed in research examining the learning experiences of PSTs in special education teacher education (Conderman et al, 2013) and general teacher education programmes (Sokal et al, 2014). In both instances, researchers found that PSTs who experienced in-depth coursework and relevant practical experiences working with students with disabilities felt better prepared to provide an inclusive learning environment than those PSTs who did not receive the same experiences.…”
Section: Physical Education Pre-service Trainingsupporting
confidence: 83%
See 1 more Smart Citation
“…They argue that well planned coursework and exposure to practical hands-on experiences play a crucial role in fostering favourable attitudes and perceptions of pre-service physical education teachers towards working with students with disabilities. Similar findings were revealed in research examining the learning experiences of PSTs in special education teacher education (Conderman et al, 2013) and general teacher education programmes (Sokal et al, 2014). In both instances, researchers found that PSTs who experienced in-depth coursework and relevant practical experiences working with students with disabilities felt better prepared to provide an inclusive learning environment than those PSTs who did not receive the same experiences.…”
Section: Physical Education Pre-service Trainingsupporting
confidence: 83%
“…Utilising such a design supports previous research identifying the importance of offering students a balance of theoretical and practical learning experiences (Stewart, 1990). During an investigation of beginning special education teachers' perceptions of their training programme, Conderman et al (2013) found that applicable courses and student teaching had the greatest impact on their preparation.…”
Section: During the Programme: 'How Am I Changing?' And 'What Is Caussupporting
confidence: 71%
“…These findings accord with other findings on the disconnection between literature targeted for special educators and that for general educators (Hazelkorn et al, 2010). Many researchers recommend enhancing preservice teachers' knowledge of and practical experiences with RTI during their teacher preparation programs, especially in-depth instruction on the implementation of all RTI components (Brownell et al, 2010;Chamberlain, 2009;Conderman & Johnston-Rodriguez, 2009;Conderman et al, 2013;Harvey et al 2010;Hazelkorn et al, 2010;Klingner & Edwards, 2006;McCombes-Tolis & Spear-Swerling, 2011;Otaiba, 2005;Pugach & Blanton, 2012). Based on our review, we suggest that teacher preparation programs enhance their focus on RTI, but peer-reviewed journals should also increase their call for publications targeting GE preservice teachers to expand the literature on RTI and GE teacher preparation.…”
Section: Discussionsupporting
confidence: 88%
“…The second article focused on recent graduates from a special education preparation program and their perceptions of their training (Conderman, Johnston-Rodriguez, Hartman, & Walker, 2013). Positive feedback was received about the strong connection between content knowledge and practical experiences during their program.…”
Section: Literature Of Rti On Special Education Teacher Preparationmentioning
confidence: 99%
“…The findings are also in line with those from another recent study, conducted by Conderman et al (2013), in which 64 beginning special educators were surveyed about their preparation program at a Midwestern university. Participants were asked how well prepared/confident they felt with regard to 25 competencies using a 4 point Likert scale (1 = not prepared/not confident; 4 = very prepared/very confident).…”
Section: Journal Of Education and Trainingsupporting
confidence: 78%